Empiric antibiotic therapy in children with community-acquired Pneumonia - Zhang, Linjie (2008)
Objective: To assess the possible change of clinical response to empiric antibiotic therapy among children survivors hospitalized with community-acquired pneumonia at a teaching hospital during 1991-2001. Methods: This was a retrospective observational study. The medical records of children (aged 29 days to 12 years) with diagnosis of presumed bacterial pneumonia at hospital discharge were reviewed and patient’s data were extracted, using standardized forms. The principal outcome was patient’s response to empiric antibiotic therapy. The secondary outcome was length of hospital stay. Results: 893 patients were included for this study. Penicillin and derivatives were the most commonly used empiric antibiotics throughout the studied period. There was a slight but statistically significant increase in the mean rate of antibiotic failure from 1991-1998 to 1999-2001 (3.8% vs 11.4%, P<0,001). The most common causes for antibiotic failure were inadequate coverage of initial antibiotics between 1991-1998 and presumed antibiotic resistance between 1999-2001. No significant difference was observed regarding the means of length of hospital stay during the whole studied period (P=0.08). Conclusion: Empiric antibiotic therapy was effective among children with community-acquired pneumonia treated at a teaching hospital between 1991-2001, inspite of a slight increase in the rate of presumed antibiotic resistance in later years.